2004
DOI: 10.4161/cbt.3.11.1217
|View full text |Cite
|
Sign up to set email alerts
|

New strategy for efficient selection of dendritic cell-tumor hybrids and clonal heterogeneity of resulting hybrids

Abstract: ABBREVIATIONS ACKNOWLEDGEMENTSWe thank Pat Adcock for her secretarial assistance. This work was supported by NIH grants AI46755 (to H. Matsue), AR35068, AR43777 and AI43232 (to A. Takashima). Research PaperNew Strategy for Efficient Selection of Dendritic Cell-Tumor Hybrids and Clonal Heterogeneity of Resulting Hybrids ABSTRACTHeterotypic hybrids created between dendritic cells (DC) and tumor cells represent an efficient approach for loading DC with tumor-associated antigens (TAA) and DC-tumor hybrid vaccines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Therefore, mature fusions have more active to stimulate CTL responses in the immunosuppressive environment in the growing tumor burden (Figure 4). Indeed, in murine models, tumor/DC fusions coadministrated with TLR9 (synthetic oligodeoxynucleotides (ODNs) containing specific bacterial unmethylated CpG motifs (CpG ODNs)) and TLR3 agonists (Poly(I:C)) significantly reduced melanoma metastasis through IL-12 production, compared with fusions alone [59, 82]. Moreover, tumor/DC fusions transduced with IL-12 [30, 87, 91, 96], IL-18 [90, 96], GM-CSF [47], IL-4 [88], CD40L [89] genes induced potentially increased therapeutic efficacy.…”
Section: Activation or Inactivation Of Antitumor Immunity By Tumormentioning
confidence: 99%
“…Therefore, mature fusions have more active to stimulate CTL responses in the immunosuppressive environment in the growing tumor burden (Figure 4). Indeed, in murine models, tumor/DC fusions coadministrated with TLR9 (synthetic oligodeoxynucleotides (ODNs) containing specific bacterial unmethylated CpG motifs (CpG ODNs)) and TLR3 agonists (Poly(I:C)) significantly reduced melanoma metastasis through IL-12 production, compared with fusions alone [59, 82]. Moreover, tumor/DC fusions transduced with IL-12 [30, 87, 91, 96], IL-18 [90, 96], GM-CSF [47], IL-4 [88], CD40L [89] genes induced potentially increased therapeutic efficacy.…”
Section: Activation or Inactivation Of Antitumor Immunity By Tumormentioning
confidence: 99%
“…Therefore, the fusions vaccine may represent an effective strategy for the treatment of human tumors. The DCs/tumor fusions vaccine not only provided protection against challenge with tumor cell, but also regressed the established tumors, including melanoma [11, 19, 24, 3640], colorectal [12, 20, 34, 4148], breast [4953], esophageal [54], pancreatic [55], hepatocellular [5660], lung [61, 62], laryngeal [63], renal cell carcinoma [64], sarcoma [6567], myeloma [6873], mastocytoma [74], and neuroblastoma [75]. …”
Section: Induction Of Ctl Responses By Dcs/tumor Fusions In Animalmentioning
confidence: 99%
“…Indeed, DCs/tumor fusion cell vaccines have been shown to possess the elements essential for processing and presenting tumor antigens to host immune cells for inducing effective antitumor immune response and for breaking T-cell tolerance to tumor-associated antigens in animal models [12, 20]. Many animal studies have demonstrated that the DCs/tumor fusion vaccine not only provided protection against challenge with tumor cells, but also regressed established tumors, including melanoma [21–27], colorectal [1214, 18, 2835], breast [3639], esophageal [40], pancreatic [41], hepatocellular [4246], lung [47, 48], laryngeal [49], renal cell carcinoma [50], sarcoma [5153], myeloma [5459], mastocytoma [60], and neuroblastoma [61]. …”
Section: Antitumor Immunity By Dcs/tumor Fusions In Animal Modelmentioning
confidence: 99%